STRATEGI PEMBELAJARAN GITAR KLASIK DALAM PERLOMBAN FLS2N TINGKAT KOTA SERANG DI PROVINSI BANTEN - Syamsul Rizal; Vivi Ervina Dewi (JPKS (Jurnal Pendidikan dan Kajian Seni), 2023)
Abstract: Learning classical guitar has its own level of difficulty when it comes to playing a song. Starting from right-handed or left-handed playing techniques, such as tirando, apoyando, arpeggio, scale, slur, and slide techniques. So that a teacher must have a strategy in delivering learning material to his students. So, to achieve maximum results in a classical guitar learning, a teacher must have a special strategy in achieving learning objectives. This article aims to analyze the classical guitar learning strategies used by Dandi Musa in providing material to his students. This study uses a qualitative method with a phenomenological approach. The subjects of this research are Dandi Musa as a classical guitar teacher and Aida Mulya L. and Raissa Bamban as students. Data collection through in-depth interviews, observation, and documentation. Data analysis using data reduction, data presentation, and conclusions. The results of this study state that the strategy in classical guitar learning used by Dandi Musa is structured. Namely through introduction strategies, core learning strategies, and learning evaluation strategies. so that through this strategy the learning outcomes are maximized.